ANALISIS PERILAKU KONSUMEN TERHADAP PRODUK LOKAL DI KOTA BINJAI: PENDEKATAN EKONOMI MIKRO - Suwandi Suwandi; Budi Abdullah; Rido Kurniawan; Dani Aulia Rahman Lubis (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze consumer behavior towards local products in Binjai City through a microeconomic approach, focusing on factors influencing purchasing decisions and their relationship to the social and cultural aspects of the community. The research method used is qualitative, with in-depth interviews conducted with 20 key informants consisting of consumers, sellers, and local producers. The data obtained were validated through source triangulation, namely by comparing the results of interviews, field observations, and secondary documents such as regional trade reports in Binjai City. The research results show that consumer behavior towards local products in Binjai City is influenced by two main dimensions: economic rationality (price, quality, and product utility) and socio-cultural factors (local identity, community solidarity, and regional pride). Consumers purchase products not only based on their economic utility but also on their inherent symbolic and social values. Furthermore, the study found information asymmetry and limited market innovation that influence consumer trust in local products. Some consumers still consider local products less competitive than national products due to a lack of information about quality and production standards. From a microeconomic perspective, this phenomenon suggests that consumer behavior in Binjai reflects bounded rationality economic decisions are not solely based on efficiency but also on the surrounding social and cultural context.